Simultaneous reduction of all ORMDL proteins decreases the threshold of mast cell activation - Demkova, Livia; Bugajev, Viktor; Utekal, Pavol; Kuchar, Ladislav; Schuster, Björn; Draber, Petr; Halova, Ivana (Scientific reports, 2023)
In mammals, the ORMDL family of evolutionarily conserved sphingolipid regulators consists of three highly homologous members, ORMDL1, ORMDL2 and ORMDL3. ORMDL3 gene has been associated with childhood-onset asthma and other inflammatory diseases in which mast cells play an important role. We previously described increased IgE-mediated activation of mast cells with simultaneous deletions of ORMDL2 and ORMDL3 proteins. In this study, we prepared mice with Ormdl1 knockout and thereafter, produced primary mast cells with reduced expression of one, two or all three ORMDL proteins. The lone deletion of ORMDL1, or in combination with ORMDL2, had no effect on sphingolipid metabolism nor IgE-antigen dependent responses in mast cells. Double ORMDL1 and ORMDL3 knockout mast cells displayed enhanced IgE-mediated calcium responses and cytokine production. Silencing of ORMDL3 in mast cells after maturation increased their sensitivity to antigen. Mast cells with reduced levels of all three ORMDL proteins demonstrated pro-inflammatory responses even in the absence of antigen activation. Overall, our results show that reduced levels of ORMDL proteins shift mast cells towards a pro-inflammatory phenotype, which is predominantly dependent on the levels of ORMDL3 expression.
Keywords: prezentace antigenu; mastocyty; imunoglobulin E; sfingolipidy; Animals; Membrane Proteins; Mast Cells; Sphingolipids; zvířata; Mice; Immunoglobulin E; Antigen Presentation; membránové proteiny; myši